True-color 3D surface metrology for additive manufacturing using interference microscopy - DiSciacca, Jack; Gomez, Carlos; Thompson, Adam; Lawes, Simon; Leach, Richard; Colonna de Lega, Xavier; de Groot, Peter (2017)
Coherence scanning interferometry (CSI) is widely used for surface topography characterisation. With the ability to measure both rough surfaces with the high slopes and optical finishes, CSI has made contibutions in fields from industrial machining to optical fabrication and polishing [1,2]. While the low coherence sources for CSI are typically broadband and suitable for color imaging, the metrology is usually performed without regards for the color information [3]. We present color surface topography measurements from a CSI instrument designed to provide true color images in addition to areal surface topography of additive manufactired samples. The addition of color measurements enables contamination and defect detection along with blemish and discoloration identification.